Leverage and Feedback Effects on Multifactor Wishart Stochastic Volatility for Option Pricing - Manabu Asai; Michael McAleer (Tinbergen Institute, 2013)
The paper proposes a general asymmetric multifactor Wishart stochastic volatility (AMWSV) diffusion process which accommodates leverage, feedback effects and multifactor for the covariance process. The paper gives the closed-form solution for the conditional and unconditional Laplace transform of the AMWSV models. The paper also suggests estimating the AMWSV model by the generalized method of moments using information not only of stock prices but also of realized volatilities and co-volatilities. The empirical results for the bivariate data of the NASDAQ 100 and S&P500 indices show that the general AMWSV model is preferred among several nested models.
urn:NBN:nl:ui:15-1765/38222
Keywords: C32; C51; G13; 330; Multivariate Stochastic Volatility; Wishart Process; Leverage Effects; Feedback Effects; Multifactor Model; Option Pricing; Optionsgeschäft; Stochastischer Prozess; Volatilität; Theorie; Schätzung; USA